Development of an active biodegradable film containing tocopherol and avocado peel extract - J.C.F. Fidelis; A.R.G. Monteiro; M.R.S. Scapim; C.C.F. Monteiro; D.R. Morais; T. Claus; J.V. Visentainer; F. Yamashita (Chiriotti Editori, 2015)
Thermoplastic starch (TPS) films and poly(butylene adipate co-terephthalate) (PBAT) (60/40 m/m) containing TOCO-70 (tocopherol/soybean oil 70/30 m/m) and avocado peel extract (ExA) were produced using blown film extrusion. The formulations of the 5 films (FC/F1/F2/F3 and F4) were established through mixture design with constraints maintaining constant PBAT and TPS proportion, and varying the antioxidant concentrations. Adding antioxidants reduced the water vapour permeability (Kw) of the films, with formulation F2 presenting higher decrease in relation to FC, 77.8%. The presence of ExA improved the mechanical properties of the films. The production of the films was determined to be viable after they presented good processability in a pilot extruder, as well as mechanical properties appropriate to production and utilization in industry. The presence of ExA and TOCO 70 provided the films with antioxidant activity; their application as active packaging requires further studies.